RuO2 sub‐nanocluster decorated Co3O4 as efficient and pH‐universal oxygen evolution electrocatalyst - Ziye Li; Yangfan Liu; Jiandong Hu; Wenhui Luo; Yang Wang; Zhao Xin; Yanlin Jia; Yong Pang; Hong Zhang; Zhi Liang Zhao; Yejun Li; Qi Wang (InfoMat)
Abstract Developing cost‐effective and highly efficient oxygen evolution reaction (OER) electrocatalysts that operate in both acidic and alkaline media is crucial for industrial electrocatalytic water splitting. However, achieving high performance under dual pH conditions remains a significant challenge. Herein, we report the synthesis of multi‐sized RuO2 sub‐nanoclusters on Co3O4 nanoarrays via a facile method, which demonstrates exceptional OER activity in both acidic and alkaline environments. The optimized catalyst exhibits remarkably low overpotentials of 165 mV in 0.5 M H2SO4 and 223 mV in 1 M KOH at a current density of 10 mA cm−2, respectively. Additionally, it exhibits outstanding stability, maintaining performance over a 10‐h continuous operation, which is attributed to the robust structural stability of the dispersed RuO2 sub‐nanocluster morphology. Atomic‐scale investigations reveal a layer‐by‐layer growth mechanism of Ru on the Co3O4 substrate, transitioning from single atoms to monolayer clusters and ultimately to sub‐nanoclusters as Ru loading increases. This growth mechanism provides a rational strategy for the precise design and synthesis of advanced cluster‐based catalysts. Density functional theory (DFT) calculations further elucidate the strong oxide‐support interactions between RuO2 clusters and the Co3O4 matrix, facilitating electron transfer from RuO2 to Co3O4 and generating an electron‐deficient region. This electronic modulation enhances –OH adsorption and accelerates OER kinetics. These findings underscore the potential of metal sub‐nanoclusters for designing highly efficient and durable electrocatalysts for water electrolysis.